CDS market structure and bond spreads - Andrada Bilan; Yalın Gündüz (Deutsche Bundesbank, 2022)
We study the response of bond spreads to a liquidity supply shock in the credit default swap (CDS) market. Our identification strategy exploits the exogenous exit of a large dealer from the single-name CDS market as well as granular data on CDS transactions and bond portfolio holdings of German investors. Following the shock, CDS market liquidity declines and bond spreads increase, especially for the reference firms intermediated by the dealer. Individual portfolio data indicate hedging motives as a mechanism: as CDS insurance on their bond holdings becomes costlier, investors offload the bonds. Our results therefore show that frictions in derivative markets affect the underlying securities, which can raise firms' cost of capital.
Keywords: G11; G18; G20; G28; 330; credit default swaps; dealer markets; bonds markets; creditrisk; Depository Trust and Clearing Corporation (DTCC)